2019
DOI: 10.1002/solr.201900314
|View full text |Cite
|
Sign up to set email alerts
|

Improved Interface Charge Extraction by Double Electron Transport Layers for High‐Efficient Planar Perovskite Solar Cells

Abstract: Charge extraction by electron transport layers (ETLs) plays a vital role in improving the performance of perovskite solar cells (PSCs). Here, PSCs with four different types of ETLs, such as SnO 2 , amorphous-Zn 2 SnO 4 (am-ZTO), am-ZTO/SnO 2 , and SnO 2 /am-ZTO, are successfully synthesized. The interface recombination behavior and the charge transport properties of the devices affected by four types of ETLs are systematically investigated. For dual am-ZTO/SnO 2 ETLs, compact am-ZTO ETL prepared by the pulsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…[277] These double-layer ESLs can either be in homojunction form such as Sb-doped SnO 2 /SnO 2 , [278] or in heterojunction form such as SnO 2 /TiO 2 , [279] SnO 2 /2D TiS 2 , [280] amorphous-WO x /SnO 2 , [281] or amorphous Zn 2 SnO 4 (a-ZTO)/SnO 2 . [282] Such stacks target the improvement of at least one parameter of SnO 2 contacts, as shown in Table 7. For example, SnO 2 /TiO 2 contacts can provide a band alignment gradient, [279] whereas, SnO 2 /2D TiS 2 (with ultrathin 5 nm TiS 2 ) can establish a better interface with a strong chemical affinity of Pb for SO 4 2− groups and passivate trap states.…”
Section: Double-layer Configuration Of Sno 2 With Other Metal Oxide Layersmentioning
confidence: 99%
“…[277] These double-layer ESLs can either be in homojunction form such as Sb-doped SnO 2 /SnO 2 , [278] or in heterojunction form such as SnO 2 /TiO 2 , [279] SnO 2 /2D TiS 2 , [280] amorphous-WO x /SnO 2 , [281] or amorphous Zn 2 SnO 4 (a-ZTO)/SnO 2 . [282] Such stacks target the improvement of at least one parameter of SnO 2 contacts, as shown in Table 7. For example, SnO 2 /TiO 2 contacts can provide a band alignment gradient, [279] whereas, SnO 2 /2D TiS 2 (with ultrathin 5 nm TiS 2 ) can establish a better interface with a strong chemical affinity of Pb for SO 4 2− groups and passivate trap states.…”
Section: Double-layer Configuration Of Sno 2 With Other Metal Oxide Layersmentioning
confidence: 99%
“…Figure f depicted the V oc versus light intensity ( I ) linear relationship to illustrate the charge recombination process under open-circuit conditions, which had the same trend corresponding to Figure e according to eq : Theoretically, n close to 1 suggested that the radiative recombination predominates, and when n was close to 2, it indicated the impact of trap-assisted Shockley–Read–Hall (SRH) recombination. , In Figure f, the slope of the SnO 2 -Li device (1.38 k B T / q ) was significantly lower than the control device (1.80 k B T / q ). The decreased slope value implied less trap-assisted SRH recombination and better charge transport.…”
Section: Resultsmentioning
confidence: 73%
“…The relationship between Voc and light intensity (I) was fitted and shown in Figure 5h. The ideal factor (n) was identified, n by plotting the Voc as a function of light intensity and using the following equation: [41,42] V q ln 1 nkBT I oc…”
Section: Resultsmentioning
confidence: 99%